2016
DOI: 10.1021/acs.jchemed.6b00189
|View full text |Cite
|
Sign up to set email alerts
|

“Greening” a Familiar General Chemistry Experiment: Coffee Cup Calorimetry to Determine the Enthalpy of Neutralization of an Acid–Base Reaction and the Specific Heat Capacity of Metals

Abstract: Coffee cup calorimetry, performed with calorimeters made with styrofoam coffee cups, is a familiar experiment in the general chemistry laboratory. These calorimeters are inexpensive, easy to use, and provide good insulation for most thermodynamics experiments. This paper presents the successful substitution of paper coffee cups for styrofoam cups to construct homemade calorimeters. Important modifications to the experimental protocol when using paper cup calorimeters are discussed. Data collected using calorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…■ DATA AND ANALYSIS Alkalinity Students' familiarity with spreadsheet use from previous experiments 98,100,101,111,115,116 was instrumental in tackling this involved data analysis. Only a handful of students had taken calculus previously.…”
Section: ■ Hazardsmentioning
confidence: 99%
“…■ DATA AND ANALYSIS Alkalinity Students' familiarity with spreadsheet use from previous experiments 98,100,101,111,115,116 was instrumental in tackling this involved data analysis. Only a handful of students had taken calculus previously.…”
Section: ■ Hazardsmentioning
confidence: 99%
“…Chemical educators should continue to refine laboratory curricula to reflect these principles. Increasing evidence suggests that laboratory courses improve students' knowledge of scientific methods, and engagement with chemistry [7,8]. These courses enhance the ability to think scientifically and critically, as well as to communicate effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing core topics with sustainability has been achieved through the efforts of initiatives such as Green Chemistry Education. 68 While sustainable concepts and green chemistry have been primarily showcased in upper level elective 69,70 and organic chemistry lab courses, 71,72,73,74 efforts have been made to expand the curriculum into introductory 75,76,77 and general chemistry courses. 78,79,80 The lack of green chemistry content in organic chemistry textbooks has been explored and it has been suggested that connections to societal issues and sustainability contribute to the development of leadership skills.…”
Section: Key Takeawaysmentioning
confidence: 99%